PENGARUH PEMBELAJARAN COOPERATIVE TYPE SCRIPT TERHADAP KEMAMPUAN KERJASAMA DAN HASIL BELAJAR SISWA KELAS VIII SMP - Anggun Sri Aisya Lele; Maria Goretty D. Bantas; Maria Trisna Sero Wondo (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research aims to determine: 1) The influence of the Cooperative script-type learning model on student collaboration in the material on two-variable linear equations for class VIII SMP Muhammadiyah Ende; 2) The influence of the Cooperative script-type learning model on student learning outcomes in two-variable linear equations material for class VIII Muhammadiyah Ende Middle School; 3) The influence of the script type Cooperative learning model on cooperation and student learning outcomes in two-variable linear equations material for class VIII Muhammadiyah Ende Middle School. The type of research used is quantitative research, the location of this research is at Muhammadiyah Ende Middle School. The sample in this study was 46 people consisting of 24 people in the Experiment class and 22 people in the Control class. The instruments used were questionnaires and tests on student learning outcomes. The analysis techniques in this research are hypothesis prerequisite testing (normality test and homogeneity test) and hypothesis testing (t-test and ANOVA test). The research results found that (1) there was a significant influence between the script-type cooperative learning model on students' cooperation abilities in class VIII mathematics subjects at Muhammadiyah Ende Middle School as proven by the t-test calculation which showed that the Sig. (2-tailed) is <0.001, which means it is smaller than <0.05; (2) there is a significant influence between the script-type cooperative learning model on the learning outcomes of Muhammadiyah Ende Middle School students as proven by the t-test calculation which shows the Sig value. (2-tailed) is 0.007 which means it is smaller than <0.05; (3) there is a significant influence between the script-type cooperative learning model, the ability to collaborate and the learning outcomes of class VIII students at Muhammadiyah Ende Middle School as proven by the ANOVA test calculation which shows the Sig value. (2-tailed) is 0.000, which means it is smaller than <0.05.